Reason, Revelation, and the Civic Order : Political Philosophy and the Claims of Faith - DeHart, Paul R., 1975-; Holloway, Carson, 1969- (Book collections on Project MUSE., 2014)
While the dominant approaches to the current study of political philosophy are various, with some friendlier to religious belief than others, almost all place constraints on the philosophic and political role of revelation. Mainstream secular political theorists do not entirely disregard religion. But to the extent that they pay attention, their treatment of religious belief is seen more as a political or philosophic problem to be addressed rather than as a positive body of thought from which we might derive important insights about the nature of politics and the truth of the human condition.In a one-of-a-kind collection, DeHart and Holloway bring together leading scholars from various fields, including political science, philosophy, and theology, to challenge the prevailing orthodoxy and to demonstrate the role that religion can and does play in political life. Contributing authors include such important thinkers as Peter Augustine Lawler, Robert C. Koons, J. Budziszewski, Francis J. Beckwith, and James Stoner.